Do social interactions in the classroom improve academic attainment? - Shqiponja Telhaj (IZA World of Labor, 2018)
The role of social interactions in modifying individual behavior is central to many fields of social science. In education, one essential aspect is that “good” peers can potentially improve students' academic achievement, career choices, or labor market outcomes later in life. Indeed, evidence suggests that good peers are important in raising student attainment, both in compulsory schooling and university. Interventions that change the ability group composition in ways that improve student educational outcomes without exacerbating inequality therefore offer a promising basis for education policies.
Keywords: I24; I26; 330; education; peer effects; ability grouping; student performance; peer mechanisms